KLASIFIKASI ANAK BERKEBUTUHAN KHUSUS TUNAGRAHITA MENGGUNAKAN METODE ALGORITMA C4.5 - I Made Dananjaya Priyatama; Ridwansyah Ridwansyah (Paradigma, 2022)
Children with mental retardation are children who have differences from other children that can be seen significantly with our naked eyes, because they are children with special needs both mentally, physically and can be seen from their psychology. Intellectuals of mentally retarded children are socially slower to do everything in achieving the goals they want optimally. Children with mental retardation usually have disorders such as speech disorders or physical and mental disabilities, as well as uncontrollable emotions. The problems that exist with teachers of children with special needs are because many teachers do not know the characteristics of mentally retarded children and how to handle them through IQ levels and several other factors. In solving problems for children with special needs, these children need to be classified due to their differences from one person to another in developmental delays and physical conditions they experience, so it is necessary to distinguish educational or teaching strategies that are designed and programmed for them. With the C4.5 algorithm method, which can classify children with special needs based on existing characteristics with data that is tested with a model that is used cross validation and evaluated with a confusion matrix. Based on the results of testing with this method, the accuracy obtained is very high so that it can be used by teaching staff from the accurate information.